Struktur Komunitas Makrozoobentos di Perairan Sungai Musi Kawasan Pulokerto sebagai Instrumen Biomonitoring - Zulkifli, Hilda; Setiawan, Doni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The Pulokerto region has been planned for agrocity tourism by the Palembang City Government. The changing function of these areas givesome effects to quality of water and biota around the river. The aims of this research is to study of macrozoobenthos structure communityas biomonitoring instrument. The research was conducted during September until December 2010. The location sampling was determinedby purpossive random sampling method in 8 stations. The sampling in the moody area was carried out by Eckman grab. The results showedthat 14 genera have been classified into 5 classes such as Oligochaeta, Gastropoda, Insecta, Bivalvia and Crustacea. Population og. generais in around 75-600 ind/m 2. Diversity index is low until moderate with value 0.27-0.74 and there is no domination of species in thecommunity. The cluster analysis showed that 2 community groups of macrozoobenthos have relation with population of individu tophysicochemical quality of water. The overall study shows the balancing of community in the Pulokerto region but still susceptible topressure effect of environment.